Altered Connectivity of the Frontoparietal Network During Attention Processing in Prolactinomas - Cao, Chenglong; Wang, Yu; Liu, Jia; Chen, Aobo; Lu, Jinjiang; Xu, Guozheng; Song, Jian (Frontiers in Neurology, 2021)
Prolactinomas have been reported for the failure of cognitive functions. However, the electrophysiological mechanisms of attention processing in prolactinomas remain unclear. In a visual mission, we monitored the participants’ scalp electroencephalography (EEG). Compared to the healthy controls (HCs), larger frontoparietal theta and alpha coherence were found in the patients, especially in the right-lateralized hemisphere, which indicated a deficit in attention processing. Moreover, the frontoparietal coherence was positively correlated with altered prolactin (PRL) levels, implying the significance of PRL for adaptive brain compensation in prolactinomas. Taken together, this research showed the variations in attention processing between the HCs and prolactinomas. The coherence between frontal and parietal regions may be one of the possible electrophysiological biomarkers for detecting deficient attention processing in prolactinomas.